2020
DOI: 10.3389/fmicb.2020.00022
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Sinorhizobium (Ensifer) meliloti Bacteriophages in the Rhizosphere of Medicago marina: Myoviruses, Filamentous and N4-Like Podovirus

Abstract: Using different Sinorhizobium meliloti strains as hosts, we isolated eight new virulent phages from the rhizosphere of the coastal legume Medicago marina. Half of the isolated phages showed a very narrow host range while the other half exhibited a wider host range within the strains tested. Electron microscopy studies showed that phages M_ort18, M_sf1.2, and M_sf3.33 belonged to the Myoviridae family with feature long, contractile tails and icosaedral head. Phages I_sf3.21 and I_sf3.10T appeared to have filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Rhizobium symbioses exist within a situation of exploitation by various forms of parasites that can either be pathogenic or non-pathogenic (Brader et al, 2017). The main pathogens that directly affect Rhizobium cells are bacteriophage viruses (Werquin et al, 1988;Santamaría et al, 2014;Cubo et al, 2020). Phytopathogenic viruses infect leguminous shoots and root nodules resulting in reduced nodule biomass, premature nodule decay, low leghemoglobin content, and hence impaired nitrogen fixation (Orellana and Fan, 1978;Taha, 1993;Ismail and Atef, 1998;Huang, 2001;Mangeni et al, 2020).…”
Section: Pathogenic and Non-pathogenic Parasites Of Rhizobium Symbiosismentioning
confidence: 99%
“…Rhizobium symbioses exist within a situation of exploitation by various forms of parasites that can either be pathogenic or non-pathogenic (Brader et al, 2017). The main pathogens that directly affect Rhizobium cells are bacteriophage viruses (Werquin et al, 1988;Santamaría et al, 2014;Cubo et al, 2020). Phytopathogenic viruses infect leguminous shoots and root nodules resulting in reduced nodule biomass, premature nodule decay, low leghemoglobin content, and hence impaired nitrogen fixation (Orellana and Fan, 1978;Taha, 1993;Ismail and Atef, 1998;Huang, 2001;Mangeni et al, 2020).…”
Section: Pathogenic and Non-pathogenic Parasites Of Rhizobium Symbiosismentioning
confidence: 99%
“…Although a recent study has highlighted the diversity of filamentous phages and their presence in a broad range of bacterial and archaeal hosts (Roux et al, 2019), and filamentous phages have been reported to infect Sinorhizobium (Ensifer) meliloti (Cubo et al, 2020), to the best of our knowledge this is the first characterization of a filamentous prophage from the genome of a rhizobial strain. Filamentous phages currently belong to the Inoviridae family.…”
Section: Characterization Of the Stm 6018 Filamentous Prophage Genomementioning
confidence: 98%
“…Sinorhizobium meliloti belongs to Rhizobiales and is well characterized for its ability to form symbiotic nitrogen fixation nodules on leguminous plants ( 2 4 ). Though the study of the bacteriophages that infect nitrogen-fixing rhizobia has been low compared to enteric bacteria ( 5 ), there have been increasing numbers of reported S. meliloti phages and prophages ( 6 , 7 ).…”
Section: Announcementmentioning
confidence: 99%
“…Phages Aussie and StopSmel were isolated from soil collected in Fort Pierce, FL, USA ( Table 1 ). Enrichment cultures were prepared by incubating 10 grams of soil with 0.5 mL of overnight culture of host S. meliloti NRRL L-50 in 50 mL of tryptone yeast broth containing 0.45% CaCl 2 and incubated at 28°C for 48 h with shaking at 90 rpm ( 6 , 8 ). The culture was then passed through a 0.22-µm filter, and the presence of phage was determined by plaque assay.…”
Section: Announcementmentioning
confidence: 99%